From the Earth to the moon [videorecording (DVD)] - Elwes, Cary, 1962-; Field, Sally; Isaak, Chris; Tattersall, Gale; Chaikin, Andrew, 1956- (Home Box Office, 2013)
Throughout this nation's history, we have reached for the heavens and dreamed of touching the stars. Now Tom Hanks presents the dramatic story of the unforgettable Apollo missions.